A condição humana no antropoceno: princípios educativos para horizontes legítimos de convivência - Mendes, Michel (My University, 2019)
The purpose of this study is to reflect on the human condition in the Anthropocene, in order to propose educational principles that can trigger processes of emergence of legitimate horizons of coexistence for the human Epoch. In the early 2000s, Paul Crutzen and Eugene Estoermer, perceiving that the human action took on unprecedented proportions compared to big natural events of change in Earth's geological moments, decide to name the Anthropocene, the human Epoch in which we live now. The term suggests that the Earth is emerging from the current geological Epoch, the Holocene (last 11,700 years), and that this consequence is strongly caused by human activities, placing the human being as a geological strength able of transforming terrestrial ecosystems forever. The Anthropocene, as a geological Epoch, is not yet officialized by the International Union of Geological Sciences, and may become so in 2021 at the 36th International Congress of Geology in India. The traces, the geological signs that researchers seek and are anchoring their evidence for the formalization of the Epoch, are the technofossils. These fossils are generated by human action, such as concrete, aluminum and plastic, which make up the technosphere. Within this context, the preoccupation of this study goes toward the understanding of human conducts, of human relational living with its species and with the others that cohabit the biosphere. The theoretical composition of the study articulates the knowledge derived from Humberto Maturana and Ximena Dávila's Cultural Biology, as a changing reflective process of the Biology of Knowing and the Biology of Love, with those of Complexity, especially about the triad of humanity (human condition) individual/society/species, by Edgar Morin. The theoretical-methodological outline assumed in this study is inspired by the contributions of Maturana (2002a, 2002b) - with the scientific explanations; and Morin (2004, 2005) and Morin, Ciurana and Motta (2003) - with complexity as a method. The scientific explanations, according to Maturana (2002a), are second-order reformulations of the observer's experiences involved in observing and accepted by another (observer), based on their validation criteria and the description of the elements that make up the experience of the praxis of living. However, complexity as a method is a generative path to and from thought, being a reflective activity of the subject who knows, is able to learn, invent and create in and during his path. Therefore, this study proposed as a result of the recursive dynamics of my life, four educational principles that enable the emergence of legitimate horizons of coexistence for the Anthropocene: Educate for: reflective autonomy; relational conducts based on love; ecological and social conscience; and ecological and social responsibility. Considering my history of actions and my relational living with the environment, with what I see and feel in relation to the human being acting in and about the world, my wish is identify that other ways of understanding the world, through education, make possible the emergence of conscious human beings of its historical drift as part of the whole, the Earth system.
O objetivo deste estudo é refletir sobre a condição humana no Antropoceno, a fim de propor princípios educativos que possam desencadear processos de emergência de horizontes legítimos de convivência para a Época humana. No início da década de 2000, Paul Crutzen e Eugene Estoermer, entendendo que a ação humana tomou proporções nunca vistas antes, comparadas a grandes eventos naturais de mudança nos momentos geológicos da Terra, resolvem nomear de Antropoceno, a Época humana na qual se vive agora. O termo sugere que a Terra está saindo da atual Época geológica, o Holoceno (últimos 11.700 anos), e que essa consequência é fortemente ocasionada pelas atividades humanas, situando o ser humano como uma força geológica capaz de transformar, para sempre, os ecossistemas terrestres. O Antropoceno, como Época geológica, ainda não está oficializado pela União Internacional de Ciências Geológicas, podendo vir a sê-lo em 2021, no 36º Congresso Internacional de Geologia, na Índia. As marcas, os sinais geológicos que os pesquisadores procuram e estão ancorando suas evidências para que ocorra a formalização da Época, são os tecnófosseis. Estes fósseis são gerados pela ação humana, como concreto, alumínio e plástico, os quais compõem a tecnosfera. No interior desse contexto, a preocupação deste estudo se volta para a compreensão das condutas humanas, do viver relacional humano com sua espécie e com as demais que coabitam a biosfera. A composição teórica do estudo articula os conhecimentos advindos da Biologia-Cultural, de Humberto Maturana e Ximena Dávila, como processo reflexivo cambiante da Biologia do Conhecer e da Biologia do Amar, com aqueles da Complexidade, especialmente sobre a tríade do gênero humano (condição humana) indivíduo/sociedade/espécie, de Edgar Morin. O delineamento teórico-metodológico adotado neste estudo é inspirado nas contribuições de Maturana (2002a, 2002b) - com as explicações científicas; e de Morin (2004, 2005) e Morin, Ciurana e Motta (2003) - com a complexidade como método. As explicações científicas, de acordo com Maturana (2002a), são reformulações de segunda ordem das experiências do observador implicado no observar e aceitas por um outro (observador), a partir de seus critérios de validação e da descrição dos elementos que compõem a experiência da práxis do viver. Por sua vez, a complexidade como método é o caminho gerativo para e do pensamento, sendo uma atividade reflexiva do sujeito que conhece, é capaz de aprender, inventar e criar em e durante o seu caminho. Em vista disso, este estudo propôs como resultado da dinâmica recursiva de meu viver, quatro princípios educativos que possibilitam a emergência de horizontes legítimos de convivência para o Antropoceno: Educar para: a autonomia reflexiva; condutas relacionais pautadas no amar; a consciência ecológica e social; e a responsabilidade ecológica e social. Considerando meu historial de ações e meu viver relacional com o meio, com aquilo que vejo e sinto em relação ao ser humano agindo no e sobre o mundo, meu desejo é que outras maneiras de compreender o mundo, a partir da educação, possibilite a emergência de seres humanos conscientes de sua deriva histórica como parte de um todo, o sistema Terra.
Keywords: Educação; Homem; Geologia histórica; Conscientização social; Education; Human beings; Historical geology; Social skills